Early college program implementation and growth: a collaborative initiative by a state university - Yavuz, Olcay; Milburn, Trudy (Concurrent Enrollment Review, 2025)
This article explores a collaborative initiative undertaken by a state university aimed at implementing and expanding an Early College Program. The conceptual framework, practical strategies, collaborative efforts and background of this initiative are presented. With a focus on improving college access for all, the article introduces the university's efforts to promote an inclusive Early College Program accessible to high-need students in particular. This collaborative approach highlights the importance of fostering collaboration among both internal and external partners of Institutions of Higher Education (IHE). By sharing insights into the program design and implementation, the article aims to inspire similar initiatives and contribute to the ongoing dialogue promoting early college experiences for all.
Keywords: Conceptual framework; Focus (optics); Focus group; Higher education; Program evaluation; State (computer science); dept.aa; dept.edl

Impact of supervision and evaluation on the professional development of school-based speech-language pathologists - Brown, Jacqueline; Trombly, Christopher; Roitsch, Jane (Perspectives of the ASHA Special Interest Groups, 2025)
Keywords: American Speech-Language-Hearing Association; Asha; Developmental psychology; Language development; Linguistics; Medical education; Medicine; Pedagogy; Professional development; Psychology; dept.edl

“Community hoarding”: a further complication for education research? - Arafeh, Sousan (2025)
Keywords: Computer science; Hoarding (animal behavior); Medicine; dept.edl

Polish and Indian teachers’ self-efficacy and attitudes towards inclusion of children and youth with disabilities in regular classrooms - Ćwirynkało, Katarzyna; Parchomiuk, Monika; Gregory, Jess; Ravi, Sunitha; Krishnamurthy, Sita (International Journal of Inclusive Education, 2025)
Keywords: Developmental psychology; Inclusion (mineral); Mainstreaming; Mathematics education; Pedagogy; Psychology; Self-efficacy; Social psychology; Sociology; Special education; Teachers; attitudes towards inclusion; dept.edl; inclusion; self-efficacy; students with disabilities

Editorial: Further work on educational leadership and social justice - Arafeh, Sousan (Journal of Educational Leadership and Policy Studies, 2020)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

The adaptive challenge of social justice in educational leadership - Arafeh, Sousan (Journal of Educational Leadership and Policy Studies, 2020)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

Urban high school faculty members speak up: what they need from a school counseling program from school counselors and principals - Graf, Eric; Yavuz, Olcay (Journal of Educational Leadership and Policy Studies, 2023)
There is a growing emphasis to improve every student's academic, social-emotional, and career and college development as schools strive to design and deliver comprehensive counseling programs that support students' development in these areas. The purpose of this study is to explore a large urban high school teachers' counselors and admins' perspectives on improving a high-poverty urban school's counseling services to extend school leaders' and counselors' knowledge about delivering effective school counseling programs as, ultimately, success lies with an effective principal and school counselor partnership. Particularly, data from our study will allow urban school principals and school counselors to identify the high and low program needs of urban students to become college, career, and life ready. The next set of comparisons was conducted for social-emotional needs. Like academic development needs, the entire ANOVA summary tables showed non-significant differences. The findings indicated that some responses varied significantly across (1) special education faculty, (2) regular classroom teachers and (3) school counselors in terms of rating of students' counseling needs. School leaders and school counselors can apply the findings of this study to create systemic and comprehensive student services in their schools. Particularly, school leaders and counselors can apply the results in decision-making, discussions, and time allocation in prevention/education versus reactive/responsive academic and counseling services.
Keywords: Administrator Attitudes; Administrator Role; Career Readiness; College Readiness; Connecticut; Counselor Attitudes; Counselor Role; Educational Needs; High School Teachers; Poverty; Principals; School Counseling; School Counselors; Social Emotional Learning; Student Needs; Teacher Attitudes; Urban Schools; dept.edl

Targeted professional development strategies to increase teachers’ efficacy for educating students with special needs - Yavuz, Olcay (Çağdaş Yönetim Bilimleri Dergisi, 2020)
There is a significant increase in the number of students with disabilities. However, many general education teachers report that they feel ill-equipped to educate a classroom of students with diverse special education and learning needs. In this qualitative study, the structured focus group interviews were conducted to determine the PD opportunities and characteristics that general education teachers perceive to influence their sense of self-efficacy for educating students with special needs. The results of the focus group discussions revealed that there are several targeted professional development strategies to increase teachers’ efficacy for educating students with special needs. This study makes recommendations for the research supported professional development activities, focused on educating students with special needs, provided to general education teachers.
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Quantitative explorations of teacher self-efficacy towards students with special needs: Research Article - Arterbery, Denise Hart; Yavuz, Olcay (FIRE: Futuristic Implementations of Research in Education, 2020)
Teacher self-efficacy has been linked to positive student outcomes. This quantitative research study aimed to examine the mindsets and behaviors of regular education teachers concerning their ability to educate students with special needs. The modified Teacher Self Efficacy Survey was administered to general education teachers. Data revealed that general education teachers feel less efficacious for educating students with special needs in the areas of engagement, instructional strategies, and classroom management. This study makes recommendations for professional development, focused on educating students with special needs, provided to general education teachers. Particularly, the findings speak to the need for a more diverse, flexible, and comprehensive approach to implement teacher professional development activities to improve the achievement of students with special needs.
Keywords: Classroom Management; dept.eco; peer-reviewed

Higher education and the great resignation: a crisis of compounded inequities - Rivers, Yevgeniya (2023)
Keywords: SCSU-student; dept.edl

Self-Identification in Black, Red, Brown, and White: A clarion call to address medical racism in Native American communities - Boudreaux, Mary (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
This chapter provides a brief autobiographical account of her multiethnic and racial background as a Louisiana Creole in south Louisiana. The author points out that among all racial and ethnic groups in the United States, Indigenous people are the only ones that require some form of lineal Native American descent or blood quantum. The chapter provides an ancestry account of two American Indian tribes along the bayous of south Louisiana, the Chitimacha, and the United Houma Nation. While one federally recognized tribe has attempted to remove all relations to individuals of Black, Negro, or African American descent, the other has closed enrollment to new members (despite lineal descent), with the unifying factor among these communities being establishing progenitors. Finally, the author articulates how lack of access to resources related to issues such as COVID-19 has perpetuated the historical legacy of medical racism in tribal and underserved communities in the United States.
Keywords: COVID-19; Medical racism; Native American; Tribal communities; dept.edl

Teachers’ Attitudes Towards Inclusive Education: a Cross-National Exploration - Charitaki, G.; Kourti, I.; Gregory, J.L.; Ozturk, M.; Ismail, Z.; Alevriadou, A.; Soulis, S.-G.; Sakici, Ş.; Demirel, C. (Trends in Psychology, 2022)
The study aims to suggest a model for attitudes towards inclusive education that will yield a good fit across different countries. Moreover, we aim to explore the effect of years of teaching experience, educational work level of teachers, and the highest degree completed by teachers on teachers’ attitudes towards inclusion across different countries. A demographic scale and the ATTAS-mm were applied to 908 teachers employed in schools of general education or who offered parallel support and/or resources in five different countries (Greece, the UK, the USA, Malaysia, and Turkey). CFA suggested a 4-factor solution, which included the cognitive, affective, and behavioral factors that have been previously introduced by Gregory and Noto (2012), and a fourth factor, labeled overall attitudes towards teaching all students. In the cognitive factor, the UK had the most positive attitudes. TU, MA, and GR enrolled in the same cluster, and the USA had the least positive attitudes. In the affective factor, GR had the most positive attitude. MA and the USA enrolled in the same cluster and TU and the UK had the least positive attitudes. A similar pattern is observed for the behavioral factor with GR having the most positive attitude. TU and MA enrolled in the same cluster, and the USA and the UK had the least positive attitudes. Finally, years of teaching experience, educational work level, and the highest degree completed have a significant effect on teachers’ attitudes towards inclusion in all countries. Providing feedback for future research is the focal point of the discussion part. © 2022, Associação Brasileira de Psicologia.
Keywords: Affective; Attitudes; Behavioral; Cognitive; Inclusive education; Teachers; dept.edl; peer-reviewed

Improving Psychological and Emotional Well-Being of the First-Year College Students - Robinson, Dyan; Yavuz, Olcay (FIRE: Futuristic Implementations of Research in Education, 2021)
Almost half of the students who begin college are not retained at the institution in which they began. The purpose of this research was to explore the perceptions of first-year college students to improve their psychological and emotional well-being.  This quantitative study utilized the College Student Mentoring Scale that includes two interrelated constructs which are, Psychological and Emotional Support and The Existence of a Role Model. The research found that multiple factors impact first-year students' perceptions of their psychological and emotional well-being. Additional findings indicated that response levels were highest for The Existence of a Role Model.  It is the intention that this study will add to the somewhat limited research on improving the psychological and emotional well-being of first-year college students in higher education. Also, it will assist in future policies and practices by providing a foundation of the components that influence first-year student success through improving the effectiveness of peer mentoring programs.
Keywords: dept.com; dept.edl; dept.fye; first-year college students; peer-reviewed; ⛔ No DOI found

Plagiarism as a social contract, a new way to approach plagiarism - Gregory, Jess L. (Journal of Academic Ethics, 2021)
Most cases of plagiarism involve a power differential where not every person has the same ability to enter into a social contract. A social contract requires that each party understands the expectations or norms of the contract, has a voice in setting or changing the norms and has the ability to exit the contract. If those with less power want to gain power then they have to engage in activities bound by norms set by others with little or no ability to exit and no voice. Even if one determines that it is an option to choose a role that requires academic writing, even at the earliest grades, then the social contract demands a shared norm of what constitutes correct behavior. This study reviewed the abstracts of articles indexed in Google Scholar from 1999–2019 through the lens of integrative social contract theory (ISCT) and found, in the case of plagiarism, an existing consensus of correct behavior does not exist. Recommendations for establishing a social contract conclude the article.
Keywords: dept.edl; peer-reviewed

Learning in the time of COVID-19: capitalizing on the opportunity presented by the pandemic - Trombly, Christopher E. (Journal of Professional Capital and Community, 2020)
Purpose: This paper addresses the current disruption in the educational status quo ante that has been caused by the worldwide outbreak of COVID-19. Its purpose is to suggest how practicing educators, their professional associations and the university-based researchers with whom they partner might capitalize on the unanticipated opportunity to impact education policy that the pandemic presents. Design/methodology/approach: The author draws upon his own preparation and experiences – first as a long-time practitioner in the elementary and secondary school setting, then as a university professor – to offer insights and suggestions to practicing educators, their professional associations and the university-based researchers with whom they partner. Findings: Despite the unexpected challenges that the COVID-19 pandemic has presented to educators – challenges to which educators around the globe have risen admirably – the current crisis also affords practicing educators, their professional associations and the university-based researchers with whom they partner to change the status quo ante for the better. Originality/value: The particular value of this piece is twofold: its analysis of the impact of this unanticipated crisis upon education by an author who has served both in the elementary/secondary setting and at the university level, and its assertion that educators must avail themselves of this once-in-a-lifetime opportunity to change the educational status quo ante for the better. © 2020, Emerald Publishing Limited.
Keywords: Collaboration; Community; Professional judgment; dept.edl; peer-reviewed

The role of ego threat in professional growth: Fulfilling the ethical intentions of the SEED Model - Gregory, Jess L.; Mebane, Karreem A. (Educational Practice and Theory, 2020)
Schools and education in general have made an implicit and, we would assert, explicit promise to society to educate all the children in their care. Unfortunately, there are achievement gaps that illustrate how schools have broken this promise. Teacher evaluation and other accountability measures have been heralded as the answer to this problem. Educator ego threat impedes the implementation of goal-driven teacher evaluation models and, thus, ethical questions arise. To realize the noble goals of educator evaluation, leaders must attend to ethical concerns and to the human aspects of ego threat.
Keywords: Educational leadership; Ego threat; Goal-setting models; Teacher evaluation; Teacher performance; dept.edl; dept.rec; peer-reviewed

School Counseling Programs Identifying Academic Development Needs - Parzych, Jennifer L.; Generali, Margaret; Yavuz, Olcay (Journal of Education, 2021)
This study examined student, parent, and faculty perceptions of academic development needs and related comprehensive school counseling program services from four urban middle and high schools. Participants (n = 1,032) completed a survey designed to assist schools in planning and evaluating their career and college readiness programs, and exploring perceived student support needs. Statistically significant differences were observed in stakeholder perceptions among 12 identified interventions that support improved academic development, through factorial analysis of variance (ANOVA) and pairwise comparisons analysis. Findings provide valuable information about prioritizing student academic counseling services strategically and effectively, to meet program needs of students in high-poverty schools.
Keywords: academic development; college readiness; dept.csp; dept.edl; peer-reviewed; poverty; school counselors

School Leadership for Learning: Learning Theory to Improve Professional Practice - Gregory, Jess L.; Ben-Avie, Michael; Billups, Felice; Grassetti, Mary; Hesser, Tiffany; Lawlor, Jennifer Lynne; Martone, Drey; Maykel, Cheryl; Minkos, Marlena L.; Paslov, Linda; Trombly, Christopher; Tucker, Lauren; et al. (Jess L. Gregory, 2021)
Keywords: Educational leadership; School administrators; Handbooks, manuals, etc; In-service training; School administrators; In-service training; Teachers; dept.edl; dept.sed; faculty_collection